Hard alloy material with bicrystal structure and preparation method of hard alloy material

A two-stage sintering process for tungsten carbide and cobalt powders addresses the balance of hardness and toughness in cemented carbides, resulting in a material with enhanced density and performance characteristics.

CN119177388APending Publication Date: 2024-12-24HEFEI UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302417.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Conventional WC-Co cemented carbides face a challenge in achieving a balance between high hardness and high fracture toughness due to the trade-off between these properties, and existing twin-crystal structured WC-Co cemented carbides do not adequately address density performance.

Method used

A two-stage sintering process is employed for a mixed powder of tungsten carbide and cobalt, involving specific pressure and temperature controls, to produce a twin-crystal structure cemented carbide with high relative density, hardness, and fracture toughness, using a spark plasma sintering system.

Benefits of technology

The process results in a cemented carbide material with improved density, hardness, fracture toughness, and processing performance, while maintaining a twin-crystal structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177388A_ABST
    Figure CN119177388A_ABST
Patent Text Reader

Abstract

According to the hard alloy material with the bicrystal structure and the preparation method of the hard alloy material, the hard alloy material is obtained by conducting SPS on mixed powder of tungsten carbide powder and cobalt powder, two-stage sintering is adopted, namely, high pressure is adopted during low-temperature sintering, low pressure is adopted during high-temperature sintering, powder is prevented from being extruded in the sintering process, and the sintering quality of the hard alloy material is improved. Meanwhile, relatively high relative density can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of powder metallurgy, and more specifically, relates to a twin-crystal structure cemented carbide material and a preparation method thereof. Background Art

[0002] Cemented carbides are commonly used in industrial applications such as cutting tools, mechanical seal rings, stamping dies, etc. The most common components of cemented carbides are fine tungsten carbide (WC) particles, which are hard and brittle, and cobalt (Co) as a metal binder, which is relatively soft and ductile. Therefore, WC-Co cemented carbides are widely used as tool materials for cutting materials with high requirements, such as gray cast iron, ductile iron, austenitic stainless steel, nickel-based alloys, titanium alloys, etc., due to their high hardness, good fracture toughness, and excellent wear resistance even at high temperatures. The mechanical properties of WC-Co cemented carbides mainly depend on the content of Co binder phase, as well as the size and interface structure of WC grains. Generally, due to the trade-off between hardness and fracture toughness, it is difficult to prepare conventional WC-Co cemented carbides with both high hardness and high fracture toughness. However, the combination of high hardness and good toughness is an indispensable requirement in industrial applications, and the manufacture of materials with these properties remains a huge challenge.

[0003] Twin-crystal structured WC-Co cemented carbide is an effective way to balance hardness and fracture toughness. Coarse WC grains can bring high toughness, while fine WC grains can compensate for hardness loss. The twin-crystal structure gives WC-Co cemented carbide high toughness, high hardness, and good wear resistance and deformation resistance. For example, the invention patent application CN102433484A published on May 2, 2012 uses coarse grains and fine grains to evenly match the twin-crystal structured cemented carbide, so that the material has both good impact toughness and good wear resistance. However, the density performance of twin-crystal structured WC-Co cemented carbide has not been improved. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a twin-crystal structure cemented carbide material and a preparation method thereof. The cemented carbide material has the advantages of high relative density, high hardness, high fracture toughness and good processing performance.

[0005] According to a first aspect of the present invention, a twin-crystal cemented carbide material is provided, which is obtained by SPS sintering a mixed powder of tungsten carbide powder and cobalt powder, and is characterized in that a two-stage sintering is adopted, and the specific operation is as follows: setting an initial axial pressure of 5 to 20 MPa, evacuating to below 10 Pa, sintering with electricity, a heating rate of 5 to 50°C / min, a sintering temperature of 1150 to 1350°C (preferably a sintering temperature of 1200 to 1300°C), and terminating the sintering after keeping warm for 0 to 8 minutes, and cooling with the furnace; wherein, when the temperature reaches 750 to 760°C, the pressure is increased to 20 to 50 MPa; when the temperature reaches 1080 to 1100°C, the pressure is reduced to 10 to 20 MPa and maintained until the end of sintering.

[0006] Preferably, the mixed powder contains 94wt.% to 99wt.% of tungsten carbide powder and 1wt.% to 6wt.% of cobalt powder; more preferably, the mixed powder contains 95wt.% to 98wt.% of tungsten carbide powder and 2wt.% to 5wt.% of cobalt powder.

[0007] Preferably, the purity of the tungsten carbide powder is not less than 99.9%, and it is divided into two powder sizes, namely 5-15wt.% of tungsten carbide powder with a powder size of 0.4μm and 85-95wt.% of tungsten carbide powder with a powder size of 1.0-2.0μm.

[0008] Preferably, the purity of the cobalt powder is not less than 99.9% and the powder particle size is 1 μm.

[0009] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned twin-crystal structure cemented carbide material, comprising the following steps:

[0010] Step 1, powder mixing: put tungsten carbide powder and cobalt powder in a certain proportion into a cemented carbide ball mill for wet grinding and mixing, and then dry the obtained mixed powder;

[0011] Step 2, mold assembly: put the dried mixed powder into a graphite female mold, separate the graphite female mold from the mixed powder with a graphite bushing or graphite paper, separate the graphite indenter from the powder with a graphite sheet or graphite paper of the same size as the graphite indenter, wrap a layer of thermal insulation graphite felt around the assembled graphite mold, and then pre-press at a pre-pressing pressure of 5 to 20 MPa and maintain the pressure;

[0012] Step 3, sintering: Place the assembled graphite mold in the SPS system, set the initial axial pressure to 5-20 MPa, evacuate to below 10 Pa, and sinter with electricity;

[0013] Step 4, sampling: taking out the sample by using a hydraulic press, and grinding the graphite on the surface of the sample to obtain a twin-crystal structure cemented carbide block material.

[0014] The present invention performs two-stage sintering on a mixed powder of tungsten carbide powder and cobalt powder, adopts a higher pressure during low-temperature sintering, and adopts a lower pressure during high-temperature sintering, thereby avoiding the powder from being squeezed out during the sintering process and obtaining a higher relative density at the same time; the process is simple, the production process is short, the sintering temperature is low, and it is environmentally friendly; and the prepared cemented carbide material has the advantages of high relative density, high hardness, high fracture toughness, good processing performance, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a surface scanning electron microscope (SEM) photograph of the cemented carbide bulk material prepared according to Example 1. DETAILED DESCRIPTION

[0016] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0017] First, cut the graphite paper or graphite bushing according to the inner wall size of the graphite negative mold to match the graphite negative mold, ensure that the cut graphite paper and graphite bushing are completely fitted with the negative mold, then put the lower pressure head into the graphite negative mold, and put in the graphite paper or a piece of graphite sheet of the same size as the lower pressure head to make it fit the pressure head; then put the mixed powder mixed and dried in proportion into the graphite negative mold to ensure that there is no direct contact between the powder and the graphite negative mold; finally, put the graphite paper or graphite sheet and the upper pressure head on the powder in the negative mold in turn, and use a hydraulic press to apply pre-pressure and maintain pressure. After the above work is completed, use high-temperature graphite felt to wrap the mold. The size of the graphite mold and pressure head is determined by the size of the sample to be prepared.

[0018] The spark plasma sintering system used in the following embodiments is from SINTER LAND Co., Ltd. of Japan, and the models are LABOX-350 and LABOX-6020. Spark plasma sintering (SPS) includes pulse energization pressure sintering, electric field assisted sintering, pulse current rapid sintering, etc. It should be noted that the preparation and sintering of cemented carbide materials using the method of the present invention and equipment of other manufacturers and models are also within the scope of protection of the present invention.

[0019] The density results in the following examples are measured using the Archimedes drainage method; the hardness test is obtained by using a Vickers hardness tester under a load of 30 kgf and holding for 15 seconds, and the average value of 5 to 10 tests is taken as the final result; the fracture toughness test complies with the international standard ISO 28079-2009 "Hardmetals-Palmqvist toughness test", measuring and calculating the total length of the four cracks at the indentation tip, and combining the Vickers hardness value of the sample under the indentation to calculate the fracture toughness K IC .

[0020] Example 1

[0021] A φ30 mm×10 mm double crystal cemented carbide block material was prepared, wherein WC:Co=96:4. In the WC powder, WC powder with a powder size of 0.4 μm accounted for 10 wt.%, and WC powder with a powder size of 1.0 μm accounted for 90 wt.%.

[0022] 1. Mixed powder: 300 g of the powder weighed according to the above weight ratio and 210 ml of anhydrous ethanol are placed in a carbide ball mill for wet grinding, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball mill speed is 150 r / min, and the ball milling time is 24 h; the mixed powder after ball milling is subjected to high-temperature vacuum drying at a drying temperature of 75°C and a drying time of 12 h.

[0023] 2. Mold loading: Place the dried mixed powder into a graphite female mold and pre-press it with a manual hydraulic press. The pre-pressing pressure is 10 MPa and the pressure is maintained for 5 minutes.

[0024] 3. Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 10MPa, evacuate to below 10Pa, and sinter with power on; sinter at a heating rate of 30℃ / min, the sintering temperature is 1250℃, and the sintering is terminated after 6 minutes of heat preservation, and the furnace is cooled; when the temperature reaches 750℃, the pressure is increased to 40MPa, and when the temperature reaches 1100℃, the pressure is reduced to 10MPa and maintained until the end of sintering.

[0025] 4. Sampling: Take out the sample using a hydraulic press. After grinding and polishing the sample surface, a twin-crystal structure cemented carbide block material is obtained.

[0026] According to GB / T3488.2-2018, the grain size distribution of the cemented carbide block material with a twin crystal structure was statistically analyzed and the performance was tested. The statistical distribution of the grain size distribution is shown in Table 1, and the performance test is shown in Table 3. As shown in Table 1, the grain size <0.5μm accounts for 36.36%, and the grain size >0.5μm accounts for 63.64%. The sintered block has an obvious twin crystal structure.

[0027] Table 1

[0028]

[0029] Example 2

[0030] A φ30m×10mm double crystal cemented carbide block material was prepared, wherein WC:Co=96:4. In the WC powder, WC powder with a powder size of 0.4 μm accounted for 10 wt.%, and WC powder with a powder size of 2.0 μm accounted for 90 wt.%.

[0031] 1. Mixed powder: 300g of the powder weighed according to the above weight ratio is placed in a carbide ball mill with 210ml of anhydrous ethanol for wet grinding, wherein the abrasive is carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 150r / min, and the ball milling time is 24h. The powder after ball milling is dried at high temperature in vacuum at 75℃ for 12h.

[0032] 2. Mold loading: Place the dried mixed powder into a graphite female mold and pre-press it with a hydraulic press at a pre-pressing pressure of 5 MPa and maintain the pressure for 5 minutes.

[0033] 3. Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; sinter at a heating rate of 50℃ / min, the sintering temperature is 1260℃, and the sintering is terminated after 6 minutes of heat preservation, and the furnace is cooled; when the temperature reaches 760℃, the pressure is increased to 20MPa, and when the temperature reaches 1080℃, the pressure is reduced to 10MPa and maintained until the end of sintering.

[0034] 4. Sampling: Take out the sample using a hydraulic press. After grinding and polishing the sample surface, a twin-crystal structure cemented carbide block material is obtained.

[0035] According to GB / T3488.2-2018, the grain size distribution of the cemented carbide block material with a twin crystal structure was statistically analyzed and the performance was tested. The statistical distribution of the grain size distribution is shown in Table 2, and the performance test is shown in Table 3. As shown in Table 2, the grain size <0.5μm accounts for 11.47%, and the grain size >0.5μm accounts for 88.53%. The sintered block has an obvious twin crystal structure.

[0036] Table 2

[0037]

[0038] Comparative Example 1

[0039] A φ30 mm×10 mm double crystal cemented carbide block material was prepared, wherein WC:Co=96:4. In the WC powder, WC powder with a powder size of 0.4 μm accounted for 10 wt.%, and WC powder with a powder size of 1.0 μm accounted for 90 wt.%.

[0040] 1. Mixed powder: 300 g of the powder weighed in the above weight ratio and 210 ml of anhydrous ethanol are put into a carbide ball mill for wet grinding, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball mill speed is 150 r / min, and the ball milling time is 24 h; the powder after ball milling is subjected to high-temperature vacuum drying at a drying temperature of 75°C and a drying time of 12 h.

[0041] 2. Mold loading: Place the dried mixed powder into a graphite female mold and pre-press it with a manual hydraulic press. The pre-pressing pressure is 10 MPa and the pressure is maintained for 5 minutes.

[0042] 3. Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 10MPa, evacuate to below 10Pa, and sinter with power on; sinter at a heating rate of 30℃ / min, the sintering temperature is 1250℃, and the sintering is terminated after 6 minutes of heat preservation, and the furnace is cooled; when the temperature reaches 950℃, the pressure is increased to 40MPa.

[0043] 4. Sampling: The samples were taken out by hydraulic press. After grinding and polishing, the twin-crystal structure cemented carbide block material was obtained. The performance test was carried out on it. The specific performance parameters are shown in Table 3.

[0044] Table 3

[0045]

[0046] It can be seen from Table 3 that the twin-crystal structure cemented carbide material prepared by the two-step sintering method has a higher density, and the addition of coarse grains improves the fracture toughness and bending strength of the material.

[0047] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention.

Claims

1. A twin-crystal cemented carbide material, obtained by SPS sintering a mixture of tungsten carbide powder and cobalt powder, characterized in that: Two-stage sintering is adopted, and the specific operation is as follows: Set the initial axial pressure to 5-20MPa, evacuate to below 10Pa, sinter with electricity, heat up at a rate of 5-50℃ / min, sinter at 1200-1300℃, hold for 0-8min before sintering, and cool with the furnace; Among them, when the temperature reaches 750-760°C, the pressure increases to 20-50MPa; when the temperature reaches 1080-1100°C, the pressure is reduced to 10-20MPa and maintained until the sintering is completed.

2. The dual crystal structure cemented carbide material according to claim 1, characterized in that: The mixed powder contains 94 wt.% to 99 wt.% of tungsten carbide powder and 1 wt.% to 6 wt.% of cobalt powder.

3. The twin-crystal structure cemented carbide material according to claim 2, characterized in that: The purity of tungsten carbide powder is not less than 99.9%, and it is divided into two powder sizes, namely 5-15wt.% of tungsten carbide powder with a powder size of 0.4μm and 85-95wt.% of tungsten carbide powder with a powder size of 1.0-2.0μm.

4. The twin-crystal structure cemented carbide material according to claim 2, characterized in that: The purity of the cobalt powder is not less than 99.9%, and the powder particle size is 1 μm.

5. The dual crystal structure cemented carbide material according to claim 2, characterized in that: The mixed powder contains 95wt.% to 98wt.% of tungsten carbide powder and 2wt.% to 5wt.% of cobalt powder.

6. The dual-crystal structure cemented carbide material according to claim 1, characterized in that: The sintering temperature is 1200-1300°C.

7. A method for preparing a twin-crystal cemented carbide material according to claim 1, characterized in that: The steps include: Step 1, powder mixing: put tungsten carbide powder and cobalt powder in a certain proportion into a cemented carbide ball mill for wet grinding and mixing, and then dry the obtained mixed powder; Step 2, mold assembly: put the dried mixed powder into a graphite female mold, separate the graphite female mold from the mixed powder with a graphite bushing or graphite paper, separate the graphite indenter from the powder with a graphite sheet or graphite paper of the same size as the graphite indenter, wrap a layer of thermal insulation graphite felt around the assembled graphite mold, and then pre-press at a pre-pressing pressure of 5 to 20 MPa and maintain the pressure; Step 3, sintering: Place the assembled graphite mold in the SPS system, set the initial axial pressure to 5-20 MPa, evacuate to below 10 Pa, and sinter with electricity; Step 4, sampling: taking out the sample by using a hydraulic press, and grinding the graphite on the surface of the sample to obtain a twin-crystal structure cemented carbide block material.